Management of small bowel adenocarcinoma: making the most of the available evidence to inform routine practice. Issue 4 (July 2021) - Mazlom, Hadi; Teuwen, Laure-Anne; Peeters, Marc
Abstract : Purpose of review: Small bowel adenocarcinoma (SBA) is a rare disease, for which few studies have been conducted so far. Therefore, most treatment recommendations have been extrapolated from trials in colorectal cancer. In this review, we revise available data that could improve the management of SBA, with a particular focus on systemic therapy. Recent findings: For advanced/irresectable disease, first-line doublet chemotherapy remains standard of care. It is uncertain whether extending treatment to triplet chemotherapy brings added benefit. Pembrolizumab is an accepted treatment modality for mismatch repair-deficient tumors, yet might also be active in microsatellite stable tumors. More trials with immunotherapy are underway. Although there is no place for anti-EGFR monotherapy, the addition of cetuximab to chemotherapy should be investigated further. Two trials suggest an added value of bevacizumab to chemotherapy, yet larger trials are needed to confirm these data. For localized disease, the role of (neo)adjuvant chemotherapy is under investigation. Summary: For decades, patients with SBA have probably been treated suboptimal by basing treatment recommendations on data from colorectal cancer. An effort for SBA-specific trials and/or inclusion of SBA patients in basket trials is of utmost importance in order to improve outcome for these patients.